PERSEPSI MAHASANTRI PADA PRODUK DAN JASA ONLINE SHOP SHOPEE (STUDI KASUS: MAHASANTRI INTENSIF IDIA PRENDUAN) - Mashuri Toha; Jumari Jumari (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2021)
In today's world of technology, digital progress is increasingly rapid so that it has an impact on internet networks and of course this is also triggered by the large number of people who use social media (medsos), this is also used by many businessmen to reap benefits from products and services, so they take advantage of it. platform as a medium for buying and selling products and services to make it easier for the public in buying and selling transactions, in this case the media platform being studied is the Shopee Platform, a media that is currently loved by all groups, one of which is the Intensive IDIA Prenduan student who also uses the shopee platform in selling transactions. buy online. So this makes researchers interested in examining how students' perceptions of online shopee products and services. The method used in this research is a qualitative method with a descriptive type. Data collection techniques used are observation, interviews, and documentation. The results of the research regarding Mahasantri's Perceptions of online Shop products and services (Case Study of Intensive Mahasantri IDIA Prenduan), of the ten that I interviewed, mahasantri said they were satisfied, quite satisfied, and less satisfied than what they felt when mahasantri did shopping at the shop, most of them Ten students on average have a positive view of the products and services offered by the Shoppe. There are 4 perceptions of IDIA Intensive Mahasantri Prenduan on online shop shop products and services, namely, 1) Image, 2) Service Quality, 3) Price, and 4) Service Moment.